Muslim friendly facilities of the Indonesian hotel industry: A smart tourism approach - MS, MAHRNASARI; BANGSAWAN, S; MAHFUJUR RAHMAN, M.D; MOHD SHAHRIL, A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study examines the impact of Islamic practices, Muslim friendly and online customer review system, of the Indonesian hotel industry and customer’s satisfaction. The results reported an insignificant direct relationship between Muslim friendly practices and customer satisfaction whilst an indirect effect is also observed through perceived relative quality. The findings of this study are important for Muslim populated countries because it provides useful indications for the Muslim friendly practices of the hotel industry. We also insinuate more explanation about generativity of the smart tourism system’s cubage particularly to enhancement the Muslim friendly practices in the Indonesian hotel industry.